Manajemen Laba Memediasi Efek Pengungkapan CSR dan Mekanisme GCG terhadap Kinerja Keuangan - Anisa Hanif Fadia Hayya; Tantina Haryati (IPM2KPE, 2023)
This study aims to analyze earnings management actions in mediating the effects of CSR disclosure and GCG mechanisms on financial performance. This research method is a quantitative method. The data source used comes from the annual report. The research data was processed and analyzed using Warp PLS 7.0 software with the PLS-SEM analysis method. The results showed that CSR has a significant and negative effect on financial performance and earnings management, the GCG mechanism has a significant and positive effect on financial performance and earnings management, law management has a significant and positive effect on financial performance. Also, the results of the indirect effect test explain that CSR and GCG mechanisms on the company's financial performance cannot be mediated by earnings management. Keywords: CSR, Financial Performance, Profit Management, GCG Mechanism